Kemas Ulang Informasi Produk Kopi Tradisional di Nagari Koto Baru Kabupaten Solok - Rinal, Muhammad; Desriyeni, Desriyeni (Ilmu Informasi Perpustakaan dan Kearsipan, 2018)
AbstractThe research method used in this final assignment is the desktiptif method with direct observation and interviews with traditional coffee product entrepreneurs and the community in Nagari Koto Baru Solok district. Based on data analysis, it can be concluded that the steps in making repackaging of traditional information on coffee products in Nagari Koto Baru, Solok Regency are as follows: First, identify user needs, namely identifying the needs of the community. Based on the results of the interviews that have been conducted to the community in Nagari Koto Baru, Solok Regency, the community needs more information about the traditional coffee processing process in Nagari Koto Baru, Solok Regency. Besides that the community is also interested in knowing how to process traditional coffee because the coffee has a distinctive taste. Not only that, people who like to consume coffee consume sachet coffee more often than traditional coffee. This is due to the lack of attention to traditional coffee information or limited information about traditional coffee. Second, gathering information and selecting information sources by recording knowledge and collecting data from traditional coffee product entrepreneurs in Nagari Koto Baru, Solok Regency. Third, evaluating information validation, after collecting data sourced from the community and traditional coffee entrepreneurs in Nagari Koto Baru Solok Regency. Fourth, packaging information that has been obtained from the previous process into more effective and efficient information by repackaging information into the form of repackaged information products that are in line with user needs.Keywords:Â  Repack the product; coffee; Solok